Comments on Magnetically levitated micro PM motors by two types of active magnetic bearings - Assuncao, E.; Teixeira, MCM (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This note clarifies the design of proportional derivative (PD) controllers for the magnetic levitation systems of micro PM motors proposed in the above paper. It is shown that the PD controllers cannot stabilize the described levited micro motors because it is necessary to use other values of parameters for these controllers. We present necessary and sufficient conditions for the stability of the controlled systems described in the paper.
Keywords: control; derivative controllers; micro motors; stability